Response of freshwater snails to invasive crayfish varies with physiochemical exposure cues and predator experience. (6th December 2021) - Mathers, Kate L.; Guareschi, Simone; Patel, Charlie; Wood, Paul J.
Abstract: Invasive species represent one of the greatest threats to freshwater biodiversity. The successful colonisation and establishment of populations of invasive predators in waterbodies may expose the pre‐existing fauna to novel predation strategies to which they are not pre‐adapted. Despite this, there is still a paucity of information on behavioural responses within biological invasion research. Here we present the results of a series of 24‐hr mesocosm experiments that examined the handling times and responses of four Gastropoda species ( Radix balthica, Physa fontinalis, Gyraulus albus, Potamopyrgus antipodarum ) exposed to physical and chemical cues associated with the invasive crayfish, Pacifastacus leniusculus . We specifically considered four physicochemical treatments: (1) control (no cue); (2) conspecific chemical; (3) crayfish chemical; and (4) physical presence (but confined). In addition, we considered the effect of previous predator experience of the gastropod (predator naïve or aware) and additonally assessed survivourship in encounter trials. Handling time was found to vary significantly between gastropod species with survivorship from predation mirroring handling times observed. P. fontinalis required the greatest handling time (average of 58 s) and had the highest survivorship rate. In marked contrast, P. antipodarum were rapidly consumed, with an average handling time of 6 s and no individuals surviving after 4‐hr in the encounter trials. Handling time varied by gastropod size but also shell morphology. The response to the physical and chemical cues varied between gastropod species. R. balthica and P. fontinalis demonstrated vertical avoidance behaviour most readily whilst P. albus and P. antipodarum displayed active migration only to the physical presence cue. In most instances, the response was immediate with vertical migration (above the reach of the crayfish at 15 cm on the mesocosm wall) evident within an hour. Predation regime was found to exert a significant effect on the avoidance response of the gastropods. This was particularly notable in relation to the crayfish chemical cue and to a lesser extent the injured conspecific chemical cue. Predator‐naïve populations reacted with strong vertical avoidance behaviour in response to the crayfish chemical cue, whilst, in the case of P. fontinalis, predator aware individuals reacted most strongly to the conspecific chemical cue. Our results highlight the multifaceted challenge of understanding predator–prey relationships, particularly in the face of novel invasive species, and provide much‐needed evidence to begin to tackle this complex process. Gaining a better understanding of such interactions is vital in order to underpin management strategies and to enable evolutionary trajectories in invaded ecosystems to be assessed. Previous predator experience in combination with species identity are important attributes in determining predation risk when gastropod populations are exposed to novel predators and their associated predation cues.